Roman warships - Pitassi, Michael (The Boydell Press, 2011)
The Roman Imperial Navy was the most powerful maritime force ever to have existed, prior to the European naval development of relatively recent centuries. It was able to deploy huge fleets and dominate the seas around western Europe, north Africa, and the Middle East, as well as the great rivers that formed a large part of the eastern boundary of the Roman world. It secured the trade routes and maintained the communications that allowed the Roman Empire to exist. It brought previously untouchable and unreachable enemies to battle and enabled the expansion of Imperial power into areas thought ...